Pan-genomic insights into LTP gene family evolution across diploid cotton species - Lu, Yanghan; Guo, Lishuang; Wei, Zhengya; Li, Yujun; Zhang, Yue; Zheng, Juyun; Wang, Baohua; Zhou, Zhonghua; Chen, Haodong (Frontiers in Plant Science, 2025)
IntroductionLipid-transfer proteins (LTPs) are a class of small, alkaline proteins that bind and transport various lipid molecules, including fatty acids, phospholipids, glycolipids, and steroids, between phospholipid bilayers. They play crucial roles in signal transduction, stress tolerance, and plant growth and development.MethodsIn this study, based on pan-genomic data, we identified 107 LTP family members across nine diploid cotton species, comprising 45 core, 43 variable, and 19 specific genes. Synteny and selection pressure analyses clarified the evolutionary relationships among these genes, while structural variation analyses revealed that although structural variants altered gene structures, domains, and cis-acting elements, they did not significantly affect gene expression.ResultsExpression profiling further demonstrated that LTP genes exhibited distinct spatiotemporal expression patterns in cotton ovules and roots at different developmental stages.DiscussionOverall, these findings highlight both conserved and divergent evolutionary patterns of the LTP family among diploid cotton species, providing new insights into their functional diversification, adaptive evolution, and potential involvement in cotton fiber development and stress responses.